The long road ahead status report on the implementation of the ASEAN mutual recognition arrangements on professional services. - Mendoza, Dovelyn Rannveig (Asian Development Bank, 2017)
MRAs are not easy to operationalize, however. Despite progress in key areas, member states face complex challenges as they move toward full implementation. This report is the latest in a project by the Asian Development Bank and the Migration Policy Institute to improve understanding of the barriers to the free movement of professionals within ASEAN and to support the development of strategies to overcome these hurdles.